South Africa's Key Health Challenges. Issue 1 (March 2014) - Whiteside, Alan
South Africa has an estimated 6.4 million people living with HIV, with more than 2 million already on treatment. The disease emerged in South Africa at the same time as the transition to democracy began in 1990. Although the country has seen considerable advances in many social spheres, the health sector has lagged. This lag is primarily because the HIV/AIDS epidemic results in an increased burden of disease in a cohort of people who would otherwise be healthy. This article warns that the all-pervasive nature of the epidemic will put other areas of development at risk. With economic development come new threats to the health of South Africans, including noncommunicable diseases and environmental change. Service delivery remains a challenge for the government at all levels, and the demands of not only South Africans but of migrants and refugees need to be considered.